Pleural tenting in complicated primary spontaneous pneumothorax - Eren, N; Balci, AE; Eren, S (Edizioni Minerva Medica, 2004)
Aim To assess the efficacy of pleural tenting in patients with complicated primary spontaneous pneumothorax (PSP) Methods. From 1988 through 2001, 43 patients underwent operations. Mean age was 30.4 years; the male/female ratio was 9.7. Twenty-one (48.8%) underwent pleural tenting in addition to bulla excision (experimental group, EG). Twenty-two (51.2%) underwent bulla excision plus pleural abrasion (11 patients), apical. partial pleurectomy (9 patients) and complete apical pleurectomy (2 patients) (control group, CG). The most frequent symptom was chest pain (37.2%). Surgical indications were recurrence in 21 (48.8%), prolonged air leak in 12 (27.9%), failure of expansion without air leak in 6 (13.9%), high risk occupancy in 2 (4.6%) and empyema due to air leak in 2 (4.6%). Results. Air leak time was decreased by tenting (1.9 days vs 3.7 days) as well as time of drainage (4.8 vs 6.9) and hospital stay (5.8 vs 7.9). Morbidity was 9.5% in EG and 9.1% in CG. Causes of morbidity were postoperative hematoma, prolonged air leak, expansion failure and blunt posterior sinus one of each. Re-operation needed for postoperative hematoma in CG. Mean follow-up was 5.1 years and 1 (4.5%) recurrence observed in CG. Conclusion. Tenting of the dependent lung from the apical pleura after bullectomy via axillary thoracotomy lessens air leak time without recurrence and low morbidity.
Keywords: pleural tent; pneumothorax, surgery; thoracic surgery; pleura